Effects of Acute Colchicine Administration Prior to Percutaneous Coronary Intervention: COLCHICINE-PCI Randomized Trial - Shah, Binita; Pillinger, Michael; Zhong, Hua; Cronstein, Bruce; Xia, Yuhe; Lorin, Jeffrey D.; Smilowitz, Nathaniel R.; Feit, Frederick; Ratnapala, Nicole; Keller, Norma M.; Katz, Stuart D. (Circulation. Cardiovascular interventions, 2020)
Vascular injury and inflammation during percutaneous coronary intervention (PCI) are associated with increased risk of post-PCI adverse outcomes. Colchicine decreases neutrophil recruitment to sites of vascular injury. The anti-inflammatory effects of acute colchicine administration before PCI on subsequent myocardial injury are unknown. In a prospective, single-site trial, subjects referred for possible PCI (n=714) were randomized to acute preprocedural oral administration of colchicine 1.8 mg or placebo. Among the 400 subjects who underwent PCI, the primary outcome of PCI-related myocardial injury did not differ between colchicine (n=206) and placebo (n=194) groups (57.3% versus 64.2%, =0.19). The composite outcome of death, nonfatal myocardial infarction, and target vessel revascularization at 30 days (11.7% versus 12.9%, =0.82), and the outcome of PCI-related myocardial infarction defined by the Society for Cardiovascular Angiography and Interventions (2.9% versus 4.7%, =0.49) did not differ between colchicine and placebo groups. Among 280 PCI subjects in a nested inflammatory biomarker substudy, the primary biomarker end point, change in interleukin-6 concentrations did not differ between groups 1-hour post-PCI but increased less 24 hours post-PCI in the colchicine (n=141) versus placebo group (n=139; 76% [-6 to 898] versus 338% [27 to 1264], =0.02). High-sensitivity C-reactive protein concentration also increased less after 24 hours in the colchicine versus placebo groups (11% [-14 to 80] versus 66% [1 to 172], =0.001). Acute preprocedural administration of colchicine attenuated the increase in interleukin-6 and high-sensitivity C-reactive protein concentrations after PCI when compared with placebo but did not lower the risk of PCI-related myocardial injury. Registration: URL: https://www.clinicaltrials.gov; Unique Identifiers: NCT02594111, NCT01709981.